Library and students' satisfaction - Chin, Kai Wei; Leow, Sie Hue; Lim, Pui Shi; Tan, Jia Yi; Wong, Suet Ling (2018)
A library is an indispensable place in every university. The library can be the key to success of the university and the undergraduates. With the change of times, the university will improve the library services, facilities, and resources in order to achieve undergraduate’s satisfaction. The researchers have done a lot of researches to measure the satisfaction level of undergraduates, especially the undergraduates who often visit the library. The purpose of this study is to ascertain the quality of services, facilities, and resources of the UTAR library from undergraduates’ perspective. Library services, facilities, and resources bring a large impact to the students in Malaysia, especially the students who are in tertiary education. However, the library services, facilities, and resources need to make necessary improvement in order to fulfill undergraduates’ satisfaction. The survey research methods were adopted, employing the questionnaire as an instrument of data collection. The questionnaire was distributed among 393 undergraduates in UTAR library. Descriptive and inferential statistics were used in the analysis of data. A parametric test using the one-way analysis of variance (ANOVA) was used to compare the satisfaction scores amongst the respondents from the six faculties. The results of the study discovered that the respondents were only quite satisfied with the library services, facilities, and resources on the average. The respondents were relatively most satisfied with facilities (M= 3.76), followed by services and resources (M= 3.51). The results also showed no significant differences on the satisfaction on services, facilities, and resources among the respondents of the six faculties.